Relationship between cardiac autonomic dysfunction and iron status in metabolic syndrome - Munni, Halima Akter; Akter, Khaleda; Shumi, Mahfuja Begum; Begum, Shelina (Journal of Bangladesh Society of Physiologist, 2025)
Background: Metabolic syndrome (MetS) is one of the major public health challenge with potential risk for cardiac autonomic dysfunction. Iron overload in MetS further increase the risk of cardiovascular morbidity. Objectives: To observe the relationship between cardiac autonomic nerve function and iron status in MetS patients. Methods: This cross-sectional study was conducted on 35 MetS female patients aged 25 to 45 years and equal number of age and sex matched apparently healthy subjects constituted comparison group. Cardiac autonomic nerve function was assessed by analyzing frequency domain parameters of Heart Rate Variability (HRV). HRV was recorded and analyzed by a data acquisition device, Powerlab 8/35, AD instruments, Australia. For evaluation of iron status, serum iron, serum ferritin, total iron binding capacity (TIBC) and transferrin saturation (Tsat) were measured. Data were expressed as mean±SD. Statistical analysis was done by Independent sample ‘t’ test and Pearson’s correlation coefficient test as applicable. Results: In this study, resting pulse rate, systolic blood pressure (SBP), diastolic blood pressure (DBP), low frequency (LF) norm and LF/HF(high frequency) were significantly higher (p£0.001) and total power, LF power, HF power, HF norm were significantly lower (p£0.001) in MetS patients compared to healthy subjects. Among the parameters of iron status, serum ferritin was significantly higher (p£0.05) and serum TIBC was significantly lower (p£0.05) in MetS patients than healthy subjects. On correlation analysis, only the serum TIBC showed significant (p£0.05) positive correlation with total power, LF power, HF power, HF norm in MetS patients. Conclusion: This study concludes that cardiac autonomic dysfunction may be related to higher iron status in MetS. J Bangladesh Soc Physiol 2024;19(1): 1-8